If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying f(x) = 2(x + -1)(x + -3) Multiply f * x fx = 2(x + -1)(x + -3) Reorder the terms: fx = 2(-1 + x)(x + -3) Reorder the terms: fx = 2(-1 + x)(-3 + x) Multiply (-1 + x) * (-3 + x) fx = 2(-1(-3 + x) + x(-3 + x)) fx = 2((-3 * -1 + x * -1) + x(-3 + x)) fx = 2((3 + -1x) + x(-3 + x)) fx = 2(3 + -1x + (-3 * x + x * x)) fx = 2(3 + -1x + (-3x + x2)) Combine like terms: -1x + -3x = -4x fx = 2(3 + -4x + x2) fx = (3 * 2 + -4x * 2 + x2 * 2) fx = (6 + -8x + 2x2) Solving fx = 6 + -8x + 2x2 Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Divide each side by 'x'. f = 6x-1 + -8 + 2x Simplifying f = 6x-1 + -8 + 2x Reorder the terms: f = -8 + 6x-1 + 2x
| f(x)=2(x-2)(x-3) | | 8/9*8/24 | | 6w^2-3w-18= | | f(x)=2(x-3)(x-2) | | 20.159+0.52= | | -2(3s-2)-4=-2(5s+6)-3 | | 2(2x+1)=4x | | x-(x*0.05)=526300 | | 0.15x+0.05(10-x)=0.10(-9) | | f(x)=2(x-6)(x-0) | | x-(10-x)=18 | | f(x)=2(x-0)(x-6) | | f(x)=2x*x+2x-12 | | 4-10x=36-6x | | X-2+3=6+11 | | f(x)=2(x-1)(x-6) | | 3x=7x+84 | | 4x+2(x+6)=4(x-2)-26 | | 5+3x=155x | | 8v-74=7v-61 | | x^2-36=y | | 16=3y+5y | | -16x^2+70x+5=-4 | | 32=5y+3y | | x+9(x-2)=2-3(1-2x) | | x+1/2=(x-2)2-1/2 | | 0.5x+y=4.5 | | 2+3t=3+4s | | 6(2-x)-(3-x)=7(2x+3) | | 3x^2+57=0 | | a+2(a+3)=9 | | 17=4p-3 |